Strategi Perkembangan, Indikasi Penerimaan, dan Publikasi Hasil Reservasi Bahasa Anak - Nazwa Amrina; Astuti Darmayanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
This journal aims to identify language development strategies and indicators of success in receptive and expressive language in early childhood. This type of research is qualitative descriptive research, research using library research or library research methods. In conducting library research as part of this research, researchers used various written sources, namely books, articles, magazines and other documents related to the research problem. There are several languages that need to be developed in children, including receptive language and expressive language. Receptive language involves the ability to distinguish between meaningful and meaningless sounds, receptive language is the ability to listen and read. Children's expressive language is the ability to express verbal and nonverbal language. Based on the research results, several strategies can help develop receptive language, namely: (1) storytelling activities; (2) Flash cards; (3) Language games (word practice, listen-do, listen-guess, whisper and tell stories). And some strategies to help develop children's expressive language are: (1) Finger puppet play; (2) Role play.